The teacher's introduction to attachment : practical essentials for teachers, carers and school support staff - Marshall, Nicola (Jessica Kingsley Publishers, 2014)
An easy to read, easy to use introduction for teachers and school support staff which gives practical advice on how to help children with attachment difficulties in school.